Effect of non-linear thermal radiation and Cattaneo-Christov heat and mass fluxes on the flow of Williamson hybrid nanofluid over a stretching porous sheet [version 2; peer review: 1 approved, 2 approved with reservations] - Gurju Awgichew; Eshetu Haile; Asfaw Tsegaye; Hunegnaw Dessie (F1000Research)
Background Hybrid nanofluids, consisting of two distinct nanoparticles dispersed in a base fluid, are widely used in industries requiring enhanced heat and mass transfer, such as cooling systems and heat exchangers. These fluids improve thermal conductivity and fluid dynamics, leading to better heat management and energy efficiency. This study investigates the combined effects of non-linear thermal radiation, Cattaneo-Christov heat and mass fluxes, and other factors on the three-dimensional flow, heat, and mass transfer of a Williamson hybrid nanofluid. The flow occurs over a stretching porous sheet subjected to an external magnetic field, Joule heating, chemical reactions, and heat generation. Methods Copper (Cu) and aluminum oxide (Al₂O₃) nanoparticles are suspended in ethylene glycol (C₂C₆O₂) to form the hybrid nanofluid. The governing partial differential equations are transformed into ordinary differential equations using similarity transformations and solved numerically with MATLAB’s bvp4c solver. The study examines various parameters, including stretching ratio, nanoparticle volume fraction, and relaxation times for concentration and thermal effects. Results are validated against existing literature. Results The findings reveal that a higher stretching ratio reduces velocity, temperature, concentration profiles, and local Nusselt and Sherwood numbers, while also lowering skin friction and secondary velocity. Increasing nanoparticle volume fraction decreases velocity and temperature profiles but enhances skin friction, local Nusselt, and Sherwood numbers. Concentration profiles decline with higher concentration relaxation time, while temperature increases with longer thermal relaxation time. Conclusions In conclusion, Cu−Al₂O₃/C₂C₆O₂ hybrid nanofluids demonstrate superior heat and mass transfer capabilities compared to mono-nanofluids. The performance is significantly influenced by parameters such as nanoparticle volume fraction, relaxation times, and the stretching ratio, providing valuable insights for heat and mass transfer applications.